An investigation into variations in the venous drainage pattern in brains of adolescents and adults - du Toit, Francesca (Department of Human Biology, 2021)
It is well established that the brain changes dramatically in appearance during gestation and even after birth. Due to the multi-channelled origins and the number of developmental options, the adult venous system is characterised by a higher incidence of anatomical variations than the arterial system. Limited information is available on anatomical variation of the complete cerebral venous system. It is important to have an understanding of the usual drainage pattern the cerebral venous system and its anatomical variations to provide a foundation for future studies on anomalous venous structures. The extent to which fetal drainage patterns persist postnatally has yet to be established. The goal of the current study was to accurately describe the cerebral venous drainage patterns, including persistence of fetal drainage patterns in children, adolescents and adults in order to understand anatomical variations and the clinical impact during cerebrovascular interventions. For the current study 302 magnetic resonance images with contrast medium from the Groote Schuur and Red Cross Children's War Memorial Hospitals were retrospectively reviewed. The volumes of the dural venous sinuses were traced using a novel approach developed for the study. The approach included constructing 3D models of the dural venous sinuses and using the tracings for statistical and morphological analyses. No images of children met the inclusion criteria and therefore further analyses of the subset was not possible. Statistical analyses were performed to determine if there are any associations between venous sinus volume and sex, age, cerebral dominance and/or variations. Significant differences were noted for sex, dominance and variations of the cerebral venous system. The confluence of sinuses (CS) showed the most abundant number of variations. Although many studies and classifications have been made regarding the variations of these structures, there is a lack of a comprehensive classification that includes all variations. The goal of the current study was to determine the anatomical variations more comprehensively particularly at the level of the superior sagittal sinus (SSS) and confluence of sinuses. The study improved on the current literature by using contrast enhanced images as opposed to nonenhanced images or results obtained at autopsy. It is also the first study to establish a tracing protocol for venous volume to determine cerebral dominance and describe variations of the dural venous sinuses.